Physiological Effects of Cold Stress On Cardiac Function - Raghad Hasan Nafal; Mohammed Hayder Asker (American Journal of Biology and Natural Sciences, 2026)
Cold stress is an important environmental factor which may interfere with the physiological stability in mammals, especially in small animals like rabbits. Rabbits are very sensitive to low temperatures because of the high surface-area to volume ratio, and insulated area, leading to complex thermoregulatory and cardiovascular responses, to maintain the core body temperature. The review is a summary of existing scientific findings on the physiological and molecular actions of cold stress on the cardiac system in rabbit models. Exposure to cold causes significant sympathetic response that causes the heart rate to rise, blood pressure to increase, and the myocardial oxygen demand to increase. Hemodynamic changes, such as raised systemic vascular resistance, and variations in the cardiac output exert heavy burden to the myocardium. Moreover, cold stress has a considerable impact on electrophysiological stability, leading to slowing conduction, QT prolongation, and an excessively high risk of arrhythmias. At the molecular level, low temperatures increase oxidative stress, activate inflammatory signals, impair calcium transluctions, and induce apoptosis, which plays a role in structural and functional cardiac changes. Edema, vascular congestion and initial signs of myocardial remodeling are established in histological studies when exposed over a long period. The rabbits are a useful translational model because they have physiological similarities to human beings on autonomic regulation and cardiac electrophysiology. Given these mechanisms, it is possible to mention that the research of environmental cold stress on heart health offers valuable insights into the effect of cold stresses and conditions future studies on protective measures and adaptive mechanisms.